Percutaneous management of postoperative bile leaks after upper gastrointestinal surgery - Stampfl, Ulrike; Hackert, Thilo; Radeleff, Boris; Sommer, Christof-Matthias; Stampfl, Sibylle; Werner, Julia; Büchler, Markus W.; Kauczor, Hans-Ulrich; Richter, Götz Martin (CardioVascular and interventional radiology, 2011)
Purpose: This study was designed to investigate the benefit of percutaneous interventional management of patients with postoperative bile leak on clinical outcome. Primary study endpoints were closure of the bile leak and duration of percutaneous transhepatic biliary drainage (PTBD) treatment. Secondary study endpoints were necessity of additional CT-guided drainage catheter placement, course of serum CRP level as parameter for inflammation, and patients’ survival. Methods: Between January 2004 and April 2008, all patients who underwent PTBD placement after upper gastrointestinal surgery were analyzed regarding site of bile leak and previous attempt of operative bile leak repair, interval between initial surgery and PTBD placement, procedural interventional management, course of inflammation parameters, duration of PTBD therapy, PTBD-related complications, and patients’ survival. Results: Thirty patients underwent PTBD placement for treatment of postoperative bile leaks. In 12 patients (40%), PTBD was performed secondary to a surgical attempt of bile leak repair. Additional percutaneous drainage of bilomas was performed in 14 patients (47%). CRP serum level decreased from 138.1 ± 73.4 mg/l before PTBD placement to 43.5 ± 33.4 mg/l 30 days after PTBD placement. The mean duration of PTBD treatment was 55.2 ± 32.5 days in the surviving patients. In one patient, a delayed stenosis of the bile duct required balloon dilation. Two PTBD-related complications (portobiliary fistula, hepatic artery aneurysm) occurred, which were successfully treated by embolization. Overall survival was 73% (22 patients). Conclusions: PTBD treatment is an effective therapy. PTBD treatment and additional CT-guided drainage of bilomas helped to reduce intraabdominal inflammation, as shown by reduction of inflammation parameters.
Gesehen am 20.10.2022